APPLICATION OF BEST MANAGEMENT METHODS OF OIL AND GAS ENTERPRISES IN UZBEKISTAN - Akhmedova Sh.K. (Journals Park Publishing, 2023)
This article deals with the problem of applying advanced methods for managing the activities of oil and gas enterprises in Uzbekistan. The main problems faced by oil and gas companies in Uzbekistan are described, and innovative management methods are proposed that can help solve these problems. The article also describes examples of successful implementation of innovative methods for managing the activities of oil and gas enterprises in other countries. The main innovative approaches to management are considered, their advantages and disadvantages are analyzed, and ways of their implementation in the oil and gas industry of Uzbekistan are proposed.
Keywords: oil and gas enterprises, activity management, innovations, oil and gas industry, advanced methods, management, management models, management methodology, enterprise activity, oil and gas complex, oil and gas industry.